Deciphering genetic variability in melon (Cucumis melo L.) using morphological characters - Tara, Koku K; Choudhary, Harshawardhan; Yadav, Ramesh K; Kumari, Jyoti; Mishra, Dwijesh Chandra; Shankar, Kripa (Vegetable Science, 2023)
Genetic variability, heritability and genetic advance were investigated in 96 melon (Cucumis melo L.) genotypes from 4 horticulturalor 6 varietal groups using 10 quantitative traits. The results of the analysis of variance showed that there was enough variation amongthe genotypes for all the attributes. The highest phenotypic and genotypic coefficients of variations (PCV and GCV) were observed fornode to first male flower (40.98 and 31.3%), average fruit weight (36.23 and 30.8%) and total soluble solids (28.01 and 26.67%), whiledays to first male flower anthesis (10.49 and 8.85%) and days to first female flower anthesis (8.86 and 7.4%) had the least coefficientsof variations. The high difference between PCV and GCV estimates exhibited that environmental factors had more influence on traitexpression. High heritability coupled with high-moderate GAM was observed for TSS and flesh thickness, indicating that additive genesgovern these traits and that these traits could be effectively breed through selective improvement. Nine promising genotypes wereidentified for further breeding for earliness and lateness in order to extend melon supply in the market.